Influence of teacher expertise, motivation, and self-beliefs learning outcomes: a literature review - Erid Junmela; Umar Umar; Zulbahri Zulbahri; Eval Edmizal (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2025)
This literature review synthesizes empirical evidence on how teacher expertise, student learning motivation, and self-beliefs influence learning outcomes in elementary school Physical Education. A systematic search of open-access national and international studies published between 2017 and 2025 was conducted using multiple databases with keywords related to teacher competence, motivation, self-efficacy, and learning outcomes. The findings indicate that teacher expertise, encompassing pedagogical knowledge, instructional clarity, and effective feedback, serves as a foundational determinant of student engagement and motor skill development. Learning motivation, particularly intrinsic motivation, acts as a mediating factor that enhances persistence and active participation in Physical Education activities. Self-beliefs, including self-efficacy and perceived competence, consistently predict task engagement and adaptive responses to challenges. The review highlights the interplay of pedagogical quality and psychological readiness as a holistic framework for improving learning outcomes, emphasizing the need for teacher development programs and intervention-based studies to strengthen motivation and self-beliefs in students.